Notes on the systematics of micromammals from Sterkfontein, Gauteng, South Africa - Avery, D M (Bernard Price Institute for Palaeontological Research, 2000)
The micromammalian fauna from Sterkfontein Members 4 , 5E and 6 comprises 34 species. These include six insectivores, three bats, three elephant shrews and 22 rodents. Most of these taxa, or their equivalents, have been previously recorded. Four or five new additions were recovered from deposits probably belonging to Late Pleistocene Member 6, which have previously received little or no attention. Some previously recorded taxa were not found, but this was probably due to differences in identification rather than to the absence of these forms from the sample.
Keywords: micromammals; Sterkfontein; Pleistocene; systematics